Interferon Alpha Association with Neuromyelitis Optica - Nasrin Asgari; Anne Voss; Troels Steenstrup; Kirsten Ohm Kyvik; Egon Stenager; Soeren Thue Lillevang (Clinical and Developmental Immunology)
Interferon-alpha (IFN-α) has immunoregulatory functions in autoimmune inflammatory diseases. The goal of this study was to determine occurrence and clinical consequences of IFN-α in neuromyelitis optica (NMO) patients. Thirty-six NMO and 41 multiple sclerosis (MS) patients from a population-based retrospective case series were included. Expanded Disability Status Scale (EDSS) score and MRI findings determined disease activity. Linear regression was used to assess the effects of the level of IFN-α on disability (EDSS). IFN-α was determined by sensitive ELISA assays. IFN-α was detectable in sera from 9/36 NMO patients, significantly more often than in the MS group (2/41) (P=0.0197). A higher frequency of IFN-α was observed in NMO patients with acute relapse compared to NMO patients in remission (P<0.001) and compared to the MS patients with relapse (P=0.010). In NMO patients, the levels of IFN-α were significantly associated with EDSS (P=0.0062). It may be concluded that IFN-α was detectable in a subgroup of NMO patients. Association of IFN-α levels with clinical disease activity and severity suggests a role for IFN-α in disease perpetuation and may provide a plausible explanation for a negative effect of IFN-1 treatment in NMO patients.